Bodies : Sex, Violence, Disease, and Death in Contemporary Legend - Bennett, Gillian (Book collections on Project MUSE., 2005)
Because they are so often told as news, contemporary legends force us to reevaluate life as we know it. They confront us with macabre, fantastic, horrific, or hilarious characters and events that seem to come straight out of myths and folktales, but are presented as present day events. The difficulty is that it is not at all easy to decide whether these often disturbing stories should be treated as reliable or dismissed as fantasy. The legends explored in this book are some of the most bizarre, gruesome, and politically sensitive stories in the contemporary legend canon. At any moment a body m.